The network structure of intertidal meiofaunal communities from environmental DNA metabarcoding surveys in Northwest Iberia - Bellisario, Bruno (2021)
The identification of patterns and mechanisms behind species' distribution is one of the major challenges in ecology, having important outcomes for the conservation and management of ecosystems. This is especially true for those components of biodiversity providing essential ecosystem functions and for which standard surveys may underestimate their real taxonomic diversity due to high degree of cryptic diversity and inherent diagnosis difficulties, such as meiofaunal communities. Within this context, environmental DNA (eDNA) metabarcoding may provide a fast and reliable way to refine and scale-up the characterization of biological diversity in complex environmental samples, allowing to bypass issues related to biodiversity estimation. Moreover, the possibility of integrating eDNA metabarcoding-derived data with tools and methods rooted in network theory would deepen the knowledge on the structuring processes of ecological communities in ways that cannot be predicted from studying individual species/communities in isolation. Here, a sediment eDNA metabarcoding of mitochondrial cytochrome c oxidase I (COI) and nuclear hypervariable V4 region of the 18S rDNA (18S) was used to reconstruct the bipartite networks linking intertidal meiofaunal OTUs and sampling stations from three estuaries of the North-Western Iberian Peninsula. Null models were used to identify the role of environmental and spatial constraints on the structure of COI- and 18S-derived networks and to characterize the macroecological features of surveyed phyla. Our results show the feasibility of eDNA metabarcoding to capture a fair amount of diversity hard to detect with standard survey procedures and to identify hierarchical spatial structures in intertidal meiofaunal assemblages, ultimately suggesting a restricted distributional range mostly driven by niche-based processes.